Un/Commoning Pedagogies: Forging Collectivity Through Difference in the Embodied Classroom and Beyond - Chapman, Dasha A.; Dellecave, J; Jones, Adanna Kai; Kivenko, Sharon Freda; LaMothe, Mario; Weidman, Lailye; Zabriskie, Queen Meccasia (Performance Matters, 2023)
Un/Commoning Pedagogies Collective are seven dancer-scholars who centre embodied anti-racist praxis in our teaching across the fields of anthropology, sociology, African American and Africana studies, gender, sexuality and women’s studies, dance, and performance studies. Since 2019, the Un/Commoning Pedagogies Collective has engaged in consistent, process-based collaboration around teaching, scholarship, movement practice, and collegiality. We have co-authored essays, facilitated workshops, and given talks and performances. We also share syllabi, strategies, stories, milestones, failures, resources, and friendship. This writing is rooted in our ongoing collaborations and documents a co-generation of knowledge about the possibilities and tensions of teaching with and through our full-bodied selves. Moving beyond the syllabus, we offer you a glimpse into our concerns, commitments, experiences, and strategies as movement educators. We invite you to participate with us in a process of un/commoning pedagogy through embodied practice, dialogue, and reflection.